Took : a ghost story - Hahn, Mary Downing (2015)
"A witch called Old Auntie is lurking near Dan's family's new home. He doesn't believe in her at first, but is forced to accept that she is real and take action when his little sister, Erica, is 'took' to become Auntie's slave for the next fifty years"--
8+
Keywords: Witches -- Juvenile fiction; Horror tales; Fiction; Juvenile works